(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Creativity A.P. Chekhov devoted a lot of work devoted to the study of the writer towards the macrostructure of his poetics. Insufficiently questions the study of culture and art of literary works of Anton Chekhov. The paper presents an epistolary writer, which provides advice on the construction of the phrase is the key to understanding the world – text A.P. Chekhov presents the viewpoint of the author of «not to be tempted cheap beautiful.» The work is devoted to the review of individual copyright work methods A.P. Chekhov on the artwork analyzed stories «Appropriate measures», «Daddy.» In this paper the emphasis is on portraits and everyday detail, craftsmanship psychological subtext principle laconic and domestic plot of the story. Key words: